Addressing barriers to accurate discharge data quality through a co-designed educational intervention - Rachel McCauley; Anna Connolly; Anne Matthews; Marcia Kirwan (BMC Health Services Research, 2026)
Abstract Background The Hospital In-Patient Enquiry (HIPE) system is Ireland’s national administrative database for activity in publicly funded acute hospitals. It informs healthcare planning, funding allocation, and patient safety monitoring. However, Hospital-Acquired Adverse Events (HAAEs) may be underrepresented within administrative datasets due to challenges in clinical documentation, uncertainty regarding HAAE identification, and limited communication between clinicians and Administrative Health Data (AHD) coders. This study aimed to develop and pilot a co-designed educational intervention to improve documentation and coding of selected HAAEs. Methods A four-stage co-creation framework was employed, consisting of (1) evidence review, (2) data collection and stakeholder consultation, (3) co-production, and (4) prototyping. Literature and policy reviews were conducted to identify existing challenges and education associated with administrative data recording, focused on improving documentation related to three underreported HAAEs: delirium, pneumonia, and urinary tract infections. Data were collected from non-consultant hospital doctors (NCHDs) through three focus groups and discussions with consultants, and from AHD coders and managers through a national survey and policymaker consultation. Findings informed collaborative development of an educational intervention. Prototype resources were piloted with new NCHDs, and perceived acceptability and value were assessed. Results In co-creating resources, twelve NCHDs took part in focus groups and seventy-five AHD coders and managers completed a mixed-methods survey. Both groups reported barriers to data production including limited understanding of each other’s roles in data production processes. Insights informed the development of targeted educational resources designed to tie-in with existing clinical processes. In a pilot evaluation, with a further ten newly qualified NCHDs, all participants reported low confidence in completing documentation to support HAAE coding prior to the intervention. Following the intervention, all reported increased confidence and high acceptability of resources. Conclusions This study demonstrates the feasibility and acceptability of a co-designed educational intervention aimed at improving patient documentation and accurate recording of hospital-acquired adverse events. The participation of NCHDs and AHD coders supported the co-creation of resources addressing real-world documentation and coding challenges. While further evaluation across multiple sites is required, findings suggest that targeted, co-produced educational tools may contribute to improvements in administrative data quality, enhanced patient safety monitoring and healthcare planning.